CRITICAL ANALYSIS OF MAQÄ€á¹¢IDÄª TAFSÄªR ON DISASTER MITIGATION IN THE STORY OF PROPHET LÅªá¹¬: AN EXAMINATION OF THE INTERPRETATION OF Q.S. AL-á¸¤IJR: 61-74 - Anggraini, Tri Faizah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
This research is motivated by the complexity of disasters that occur in the latest era but trigger disaster mitigation responses that tend to be passive. In the Qur'an, indications of disaster mitigation are presented through the narrative LÅ«á¹ story. However, the story of LÅ«á¹ is often read with reference to the centrality of the sexuality of the Sodomites, so that aspects of disaster mitigation are often marginalized. The interpretation of Q.S al-á¸¤ijr (15):61-74 also tends to be read textually so that it does not touch the maqÈƒá¹£id aspect behind the verse. On these problems, this study seeks to answer, how the critical analysis of maqÄá¹£idi tafsÄ«r on Disaster Mitigation in Q.S al-á¸¤ijr (15): 61-74. This question intends to explore what the maqÈƒá¹£id behind the presence of disaster mitigation orders in the story of the prophet LÅ«á¹. The results showed that the maqÈƒá¹£id aspects of the verse are hifdz al-dÄ«n, hifdz al-nafs, hifdz al-nasl, hifdz al-'aql and hifdz al-mÈƒl. At the same time, the maqÈƒá¹£id dimension is the value of humanity represented in the humanism of LÅ«á¹ who helped his people and the value of freedom of choice for the people of LÅ«á¹ to follow LÅ«á¹'s da'wah by leaving the abominable act so as to obtain salvation. By using the analysis of maqÄá¹£idi tafsÄ«r, an interpretation is obtained that goes beyond the internal aspects of the text so that the purpose behind the presentation of the story of LÅ«á¹ in this verse is increasingly revealed. This makes maqÄá¹£idi tafsÄ«r bring up a unique perspective of novelty so that the principles of disaster risk management can be deduced for related institutions.